Amorphization‐Activated Copper Indium Core‐Shell Nanoparticles for Stable Syngas Production from Electrochemical CO2 Reduction. Issue 23 (26th October 2022) - Shen, Jieyi; Wang, Lishuang; He, Xuedong; Wang, Shun; Chen, Jiadong; Wang, Juan; Jin, Huile
Abstract: Electrochemical carbon dioxide reduction reaction (CO2 RR) refers to the conversion of carbon dioxide into compounds with added value through electrolysis. It is still a great challenge to design and manufacture efficient CO2 RR catalysts for desired products. Producing syngas via CO2 RR is an environmentally friendly way to reduce CO2 in the atmosphere and the dependence on fossil fuels. Herein, a new class of Cu/In2 O3 nanoparticles (NPs) with controlled phases and structures were successfully prepared as superior electrocatalysts for CO2 RR, where the CO/H2 ratios in syngas on Cu/In2 O3 NPs/C−H2 remained about 1 : 2 at a broad potential range and the total faradaic efficiency of H2 and CO always remained about 90 %. Electronic structural analysis revealed that the excellent performance was attributed to the electronic interaction between amorphous In2 O3 and Cu. This work broadens the horizons for designing and preparing fascinating electrocatalysts for CO2 RR. Abstract : CO2 RR : Cu/In2 O3 nanoparticles (NPs) catalyze the electrochemical reduction of CO2 with a stable CO/H2 selectivity of about 1 : 2 over a large potential range, achieving total faradaic efficiencies of CO and H2 around 90 %. The catalyst benefits from strong electronic interaction between Cu core and amorphous In2 O3 shell.